SDMA Grouping for 5G Systems - Costa Neto, Francisco Hugo (2019)
In this study, we investigate the problem of maximization of the total data rate of a multi-user multiple input multiple output (MU-MIMO) system. We evaluate a solution to the space-division multiple access (SDMA) grouping problem that is composed of two parts. In the first part, we partition mobile stations (MSs) into clusters of spatially correlated MSs. In the second part, we schedule MSs from different clusters to build an SDMA group so that the multi-user (MU) interference is minimized. Looking for an implementation with reduced hardware cost, we employ a hybrid beamforming scheme and analyze its impact in terms of total data rate. The analog precoder is based on the channel information obtained from clustering while different digital precoding components are considered, namely zero-forcing (ZF) and maximum ratio transmission (MRT). The simulation results indicate that the combination of a proper partition of MSs into clusters and the suitable scheduling of MSs provides a technique able to exploit spatial compatibility more effectively and reduces inter-cell interference. Moreover, when the ZF is considered as digital precoding scheme, there is an increase of the total data rate.